2005
DOI: 10.1111/j.1478-3231.2005.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of viral load and genotype in the progression of Hepatitis B‐associated liver cirrhosis to hepatocellular carcinoma

Abstract: Patients with genotype C and a continuously high HBV DNA for 5 years or more are at a high-risk group for HCC development. Maintaining continuously low HBV DNA for 3 years or more with anti-viral therapy, may be useful in preventing or delaying HCC occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…This may explain our finding that HBV-DNA level was not a factor for hepatic decompensation and HCC development. Using highly sensitive HBV-DNA assays, a control study showed that persistent HBV-DNA >5 · 10 3 copies/ml was associated with increased risk of HCC [17] and a cohort study showed that HBV viral load was the only predictor of HCC development [18]. However, earlier studies using hybridization assays also failed to show definite correlation between the incidence of HCC development and the status of HBV-DNA at enrollment [4,8,19,20].…”
Section: Discussionmentioning
confidence: 89%
“…This may explain our finding that HBV-DNA level was not a factor for hepatic decompensation and HCC development. Using highly sensitive HBV-DNA assays, a control study showed that persistent HBV-DNA >5 · 10 3 copies/ml was associated with increased risk of HCC [17] and a cohort study showed that HBV viral load was the only predictor of HCC development [18]. However, earlier studies using hybridization assays also failed to show definite correlation between the incidence of HCC development and the status of HBV-DNA at enrollment [4,8,19,20].…”
Section: Discussionmentioning
confidence: 89%
“…Fourth, the ALT level was not evaluated in the present study. However, in the previous study about the pattern of HBV DNA and ALT level, the value of cancer prediction was much higher in the assay of HBV DNA than that of ALT [6,7] .…”
Section: Discussionmentioning
confidence: 99%
“…First, the majority of studies assess the serum HBV DNA level at a single time at study entry rather than at multiple time points or at the time of HCC development. However, there is little information on the changing pattern of the serial HBV DNA levels [6,7] , although recent data from the REVEAL-HBV study demonstrated that persistently elevated serum HBV DNA levels at more than two time points is a strong predictor of HCC risk [2,8,9] . Therefore, serial pattern analysis would be important in measurement of HCC risk; data from only two points including baseline and last follow-up are inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Viral, host (sex, age and genetic susceptibility) and environmental factors may play interactive roles in hepatocarcinogenesis [7][8][9][10][11][12] . Recent studies have indicated that serum level of HBV DNA may be a risk factor for HCC [13][14][15][16] . Tang et al [17] have previously reported that adult HBV carriers who maintain high-titer serum HBV DNA are at higher risk for development of HCC.…”
Section: Introductionmentioning
confidence: 99%